2015
DOI: 10.1007/s12035-014-9082-1
|View full text |Cite
|
Sign up to set email alerts
|

Neuroglobin Expression in the Mammalian Auditory System

Abstract: The energy-yielding pathways that provide the large amounts of metabolic energy required by inner ear sensorineural cells are poorly understood. Neuroglobin (Ngb) is a neuron-specific hemoprotein of the globin family, which is suggested to be involved in oxidative energy metabolism. Here we present quantitative real-time reverse transcription PCR, in situ hybridization, immunohistochemical and Western blot evidence that neuroglobin is highly expressed in the mouse and rat cochlea. For primary cochlea neurons, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…In this aspect, Ngb is highly expressed in the cochlear nuclei and the superior olivary complex (SOC). Moreover, it was reported that Ngb is colocalized with the antioxidant neuronal protein nitric oxide synthase (NOS) in the SOC, suggesting the importance of Ngb in oxygen homeostasis and energetic metabolism in the auditory nervous system ( 113 ) (see Table 1 ). Ngb has been also involved in calcium homeostasis ( 27 ), ATP storage, inhibition of actin assembly, and response against increased hydrogen peroxide ion levels .…”
Section: Neuroprotective Potential Of Neuroglobinmentioning
confidence: 99%
“…In this aspect, Ngb is highly expressed in the cochlear nuclei and the superior olivary complex (SOC). Moreover, it was reported that Ngb is colocalized with the antioxidant neuronal protein nitric oxide synthase (NOS) in the SOC, suggesting the importance of Ngb in oxygen homeostasis and energetic metabolism in the auditory nervous system ( 113 ) (see Table 1 ). Ngb has been also involved in calcium homeostasis ( 27 ), ATP storage, inhibition of actin assembly, and response against increased hydrogen peroxide ion levels .…”
Section: Neuroprotective Potential Of Neuroglobinmentioning
confidence: 99%
“…The authors reported double-labeling in about two-thirds of the neurons only in the MHb, pedunculopontine and laterodorsal tegmental nuclei and the locus ceruleus, as well as sporadic coexpression in single neurons in some brain regions. Although we did not conduct double-immunofluorescent detection of both globins, evidence for a considerable overlap (but also for distinct differences) in the expression of Cygb and Ngb results from comparison of Cygb-data as presented here and our rodent Ngb-data as presented previously (Reuss et al, 2002 , 2016 ; Wystub et al, 2003 ; Hankeln et al, 2004 ; Laufs et al, 2004 ; Mitz et al, 2009 ; Avivi et al, 2010 ; Schneuer et al, 2012 ). In all of these cases, it is unknown whether the same cells were labeled with either antibody.…”
Section: Discussionmentioning
confidence: 63%
“…Weak to moderate immunofluorescence, relatively similar for Cygb and Ngb, were seen in some brain regions, e.g., the hypothalamus, thalamus, facial nucleus, cerebellar nuclei (Wystub et al, 2003 ), and in the SOC (Reuss et al, 2016 ). Relatively strong expression of Cygb and Ngb was found in the hippocampal pyramidal cell layer; however, their long processes were present only with Cygb-immunofluorescence while they were unseen in the Ngb-labeled material (Hankeln et al, 2004 ; Laufs et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the hexa-coordinated nature of the Fe 21 in the heme of NGB makes it difficult for the protein to release O 2 under physiologic conditions. It is generally hypothesized that Ngb may serve as an O 2 /ROS sensor/carrier or NO/ROS scavenger (Ascenzi et al, 2014;Burmester and Hankeln, 2014;Cai et al, 2016;Reuss et al, 2016).…”
Section: Role Of Neuroglobin In Hccmentioning
confidence: 99%